Evaluation of the main sensitivity drivers in relation to indoor comfort for individuals with autism spectrum disorder. Part 2: Influence of age, co-morbidities, gender and type of respondent on the stress caused by specific environmental stimuli - Marco Caniato; Luca Zaniboni; Arianna Marzi; Andrea Gasparella (Energy Reports, 2022)
Variations of environmental parameters, like thermo-hygrometric, acoustic, visual and indoor air quality can influence the sensitivities of individuals on the spectrum. This paper presents research on this issue, studied by means of questionnaires administered to parents and professional caregivers taking care of people with Autism Spectrum Disorder (ASD).The study highlights that there are clear differences if the indirect evaluations are performed by parents or professional caregivers, in relation to the specific identification of stress sources. Additionally, acoustic domain is identified as the one causing the major stress, especially caused by strong noises and particular sounds such as voices, animal sounds and impacts, and its dependence on the severity of autism is evidenced. Furthermore, a lower impact of thermal, visual and IAQ factors is determined, with the exception of some specific stimuli like light contrast (glare), high illumination, particular light sources or stale air. Finally, this paper provides evidence of the influence of age, severity of autism and co-morbidities on perceived stress.